A Novel Missense Heterozygous Mutation in NKX2-5 Gene in a Family with Congenital Septal Defects and Cardiomyopathy: Case Series and Literature Review - Zubaidi, Abdulqader Al; Al-Shamsi, Aisha (Journal of Pediatric Genetics, 2024)
Single-gene mutations are important causes of congenital heart defects in children. Mutations in the NKX2-5 gene have been recently described in the literature as a cause of septal defects and cardiomyopathy. However, the spectrum of cardiac disease associated with NKX2-5 gene mutations is variable, ranging from asymptomatic septal defects to cardiomyopathy and sudden death. In this case report, we describe a case of 2-year-old child, along with two other family members, with a novel missense heterozygous (c.544G > T p.[Val182Phe]) mutation in NKX2-5 gene consistent with the diagnosis of autosomal dominant atrial septal defects with cardiomyopathy. This report can contribute to the understanding of genotype–phenotype correlations; it emphasizes the significant clinical relevance of NKX2-5 gene defects for congenital heart defects, sudden death, and cardiomyopathy, especially in multiple affected family members. It also suggests that individuals with NKX2-5 mutations are at risk of lethal arrhythmias and conduction disorders, that is why they should be evaluated routinely to assess the need for implantable cardioverter-defibrillator or pacemaker implantation.
Keywords: NKX2-5 gene; congenital heart diseases; atrial septal defect; ventricular septal defect; cardiomyopathy